Epidemiology of genitourinary trauma in lubelskie voivodeship in Poland from 2006 to 2018 - Piotr Kamiński; Paula Jankowska; Krzysztof Jacek Jankowski; Adam Nogalski (Kazimierz Wielki University, 2020)
Intoduction Accidents and injuries are a major challenge for modern medicine. According to EUROSTAT data from 2016, accidents were the fifth most frequent cause of death among citizens of the European Union countries. Injuries of the urogenital-tract represent about 10% of all injuries, thanks to epidemiological analysis it is possible to continuously improve the effects of their treatment. Aim The aim of this study is to analyze the epidemiology of urogenital-tract injuries in 2006-2018 in Poland, in the region of Lublin Voivodeship, and to compare them with other papers on a similar subject. Material and methods The retrospective analysis was carried out on all patients with S-T diagnosis according to ICD-9 treated in hospitals in the Lublin Voivodeship in 2006-2018. The analysis was based on statistical data collected by the National Institute of Public Health - National Institute of Hygiene. There were 934 patients selected. The collected material was analyzed statistically using the STATISTICA 13.1 program. Results Out of 934 patients the vast majority were men (n=782, 83.73%), the remaining part of analyzed population was women (n=152, 16.27%). The average age of the analyzed group was 33 years 5 months, injuries were most common in 15-30 years old group. Mortality of urogenital-tract injuries in the analyzed group was 0.75%. The most frequent injuries were to the external genitals (55.4%) followed by renal (29.66%) and urethra (5.56%) bladder (3.43%). Urinary injuries were very rare. Conlusions Injuries to the urogenital-tract most often involve young men. They are relatively rare and their mortality rate is low. External genital trauma is the most common injury to the urogenital-tract, while renal injury is the most common within the urinary tract. Occasionally injuries to other organs of the urinary tract occur. The main mechanism of injury is blunt but within the lower urinary tract a significant role is played by iatrogenic injuries.